2019
DOI: 10.1371/journal.pone.0220081
|View full text |Cite
|
Sign up to set email alerts
|

Gaining ecological insight on dietary allocation among horseshoe bats through molecular primer combination

Abstract: Knowledge on the trophic interactions among predators and their prey is important in order to understand ecology and behaviour of animals. Traditionally studies on the diet composition of insectivorous bats have been based on the morphological identification of prey remains, but the accuracy of the results has been hampered due to methodological limitations. Lately, the DNA metabarcoding and High Throughput Sequencing (HTS) techniques have changed the scene since they allows prey identification to the species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
(85 reference statements)
4
18
0
Order By: Relevance
“…5) that is known to affect the Zeale primers 20,21 . Our results complement the existing broad-scale molecular dietary data of Miniopterus schreibersii 17 , and provide geographically widespread molecular insights into the dietary ecology of Myotis daubentonii, Myotis myotis, Myotis emarginatus, Myotis capaccinii, Rhinolophus euryale and Rhinolophus ferrumequinum, which to our knowledge had only been studied at local scales previously 16,[22][23][24][25] .…”
Section: Resultssupporting
confidence: 64%
“…5) that is known to affect the Zeale primers 20,21 . Our results complement the existing broad-scale molecular dietary data of Miniopterus schreibersii 17 , and provide geographically widespread molecular insights into the dietary ecology of Myotis daubentonii, Myotis myotis, Myotis emarginatus, Myotis capaccinii, Rhinolophus euryale and Rhinolophus ferrumequinum, which to our knowledge had only been studied at local scales previously 16,[22][23][24][25] .…”
Section: Resultssupporting
confidence: 64%
“…Using eDNA metabarcoding, we have shown that R. ferrumequinum diet is much more diversified than previously described by microscopic (Flanders & Jones, 2009; Jones, 1990) and molecular analyses (Alberdi et al., 2020; Aldasoro et al., 2019; Galan et al., 2018). We revealed a broader ecological and taxonomic variety of prey from the order to species levels of taxonomic resolution (519 species; 76% of the taxa affiliated at the species level).…”
Section: Discussionmentioning
confidence: 60%
“…Because it is important to minimize disturbance and stress for bats, the number of samples is critical to assess prey diversity when using eDNA metabarcoding. Future bat diet studies should rather rely on a large number of guano collected beneath colonies rather than on feces collected from captured bats (usually < 30 samples; Alberdi et al., 2020; Aldasoro et al., 2019; Bohmann et al., 2018; Galan et al., 2018; Vallejo et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of temporal trends in body size also rejects alternative interpretations, such as, for instance, the possible occurrence of any response to changes in land use, and consequently, productivity, according to the “resource rule” pattern [ 18 ]. Rhinolophus hipposideros mostly prey on dipterans and moths, which in many cases have declined due to land use change [ 40 ], so factors such as agricultural intensification, urban expansion and forest reduction and fragmentation have likely contributed to a reduction in food availability for this bat [ 41 ]. As a pest suppressor [ 42 ], R. hipposideros is also exposed to the direct and indirect effects of pesticides [ 43 ].…”
Section: Discussionmentioning
confidence: 99%